EdTech for Marginalised Learners in Southeast Asia: Perspectives from funders and providers on priorities, design, investment, and scaling considerations - Jayasinghe, Neema; Chrisani, Aprillia; Honda, Delanie; Gunawan, Clarissa Jazzlyne (EdTech Hub, 2025)
This report presents the findings of a landscape analysis of EdTech interventions designed for the Southeast Asian context. The analysis aims to understand the extent to which EdTech providers and funders in Southeast Asia address the needs of marginalised learners through their priorities in design, investment, and scaling decisions. It focuses on initiatives targeting marginalised groups and those with potential to scale. The research for the study included interviews with funders engaged in the Southeast Asian EdTech space to examine their perspective on EdTech’s impact on marginalised learners, the approaches they adopt to support inclusive solutions, and the drivers behind their investment decisions. This builds on EdTech Hub’s research for the ASEAN-UK SAGE programme, particularly on how EdTech could be used to support improvements in foundational literacy and numeracy, out-of-school children and youth, and learners with disabilities, as well as overcoming gender barriers to employment through the use of EdTech solutions. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Cost-effectiveness of digital personalised learning: Three interventions from Kenya - Anonymised for Peer Review (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Contexts of Forced Displacement: A Rapid Evidence Review - Barnes, Katrina; Katrin, L (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices for learners in contexts of forced displacement. The main aim of the review is to provide education decision-makers, funders, and implementers (among others), with a clear picture of which interventions may be the most effective in these contexts and, crucially, which implementation decisions facilitate or hinder this effectiveness. We reviewed evidence generated between 2019 and 2024 on EdTech implementations in different contexts of forced displacement. We focused on implementations aimed at primary- and secondary-age learners, as well as their teachers and caregivers. Keywords: forced displacement, refugee education, education in emergencies An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Cognitive and Learning Disabilities: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Afzal, Nimra (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with cognitive and learning disabilities. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. We discuss the nature of EdTech for learners living with cognitive and learning disabilities, the effectiveness of these initiatives, and barriers for accessing EdTech. The RER aims neither to advocate nor discourage the use of technology to support education for learners with coginitive and learning disabilities, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; cognitive disabilities; learning disabilities; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; ⛔ No INSPIRE recid found